Towards the factory 4.0? Convergence and divergence of lean models in Italian automotive plants - Angelo Moro; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper studies the interplay in terms of techno-organisational change between the adoption of I4.0 technologies and lean production systems. Leveraging on the results of two field-work analyses conducted under a collaboration with the Sabattini Foundation and the metal workers trade union FIOM in the period 2016-2018, we compare an ensemble of factories producing both high-end/highly customised and low-end products. Emerging patterns of convergence and divergence in the techno-organisational configurations of these factories confirm that this wave of technological innovation is far from leading to total automation or the digital revolution. On the contrary, it appears to be integrated into the historical trend of "leanification" of production processes in the automotive sector, despite the organisational variety shaped by the actual implementation of this production model.
Keywords: L23; L6; M54; O33; 330; Industry 4.0; Lean production; Automotive; Work organisation; Technological innovation; Organisational innovation